Understanding perspective on community health literacy for promoting the health of older adults with hypertension: a qualitative descriptive study - Saenyabutr, Chanissara; Lagampan, Sunee; Powwattana, Arpaporn; Amnatsatsue, Kwanjai (Jurnal Ners, 2024)
Introduction: This study aimed to understand the community people's experience of access, understanding, evaluation, and application of health information for self-care of hypertensive older adults, and explore the community's perspective on promoting community health literacy (CHL) on caring for hypertensive older adults. Methods: This was a qualitative descriptive study. Data were collected through focus groups and in-depth interviews in one sub-district municipality in Mahasarakham, Thailand. A total of 37 participants from older adults with hypertension, families of older adults with hypertension, and community committees were recruited based on inclusion criteria using purposive sampling. Data were then analyzed using a five-step thematic analysis. Results: Four main themes of community people's experience  emerged 1) access to health information limited by the healthcare personnel at the primary care unit (PCU), 2) understanding the health information because it is clear and familiar, and can ask the medical personnel directly, 3) do not evaluate the health information received from healthcare personnel because they trust them, and 4) applied health information to practice only taking medicine and doctor's appointments. Three main themes to promote CHL are 1) usual healthcare activities, 2) community action, and 3) nurses at PCU, village health volunteers, and community committees should be involved in playing a key role in promoting CHL. Conclusions: Cooperation with community leaders is important to promote CHL by using active learning education and creating a supportive environment focusing on encouraging older adults to perform self-care to control their health conditions.